Fostering The Changing Economic Market Demand from The View of Various Behavioral Social Personal and Economic Transformation: Empirical Evidence from A Developed Country - Rijal, Syamsu; Aggarwal, Ashwani Kumar (Jurnal Multidisiplin West Science, 2024)
The key objective of the study is to foster the changing market demand from the view of various social, behavioral, personal, and economic transformations on individual investment decisions at Shanghai and Shenzhen stock markets in China. The study used a questionnaire to survey a total of 345 investors holding stocks of listed companies at both Shanghai and Shenzhen stock exchanges. The results of the study indicate that behavioral factors, personal factors, and market factors have a significant positive impact on individual investor investment decisions in both shanghai and Shenzhen stock markets while social factors have an insignificant negative impact on individual investor investment decisions in both shanghai and Shenzhen stock markets. Chinese stakeholders will understand better the role of various social, behavioral, personal, and markets factors and their impacts on stock market performance at both Shanghai and Shenzhen stock markets. The findings have important insights for various stakeholders i.e. government, regulatory bodies, practitioners, academia, industry, and researchers.